1980
DOI: 10.1103/physrevlett.45.201
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Infrared Absorption from Molecular Monolayers with Thin Metal Overlayers

Abstract: The infrared absorption from molecular monolayers is enhanced a factor of 20 by thin metal overlayers or underlayers with use of the attenuated-total-reflection technique.The total enhancement, including contributions from the attenuated-total-reflection geometry, is almost 10 . This effect is consistent with an electric field enhancement due to collective electron resonances associated with the island nature of the thin metal films. PACS numbers: 78.30.-j The vibration@ states of molecular monolayers can be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
455
1
9

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 633 publications
(472 citation statements)
references
References 7 publications
7
455
1
9
Order By: Relevance
“…Also, nanofilms with a random morphology and high surface roughness provide extremely high enhancement of optical absorption by molecular vibrations in a broad spectral range [13,14,[71][72][73][74]. This phenomenon has been known since the discovery of SEIRA in the early 1980s and has recently achieved worldwide success because the broadband plasmon resonance matches the absorption band of the molecular analytes.…”
Section: Optical Application Of Localized Surface Plasmon: Random Nanmentioning
confidence: 99%
“…Also, nanofilms with a random morphology and high surface roughness provide extremely high enhancement of optical absorption by molecular vibrations in a broad spectral range [13,14,[71][72][73][74]. This phenomenon has been known since the discovery of SEIRA in the early 1980s and has recently achieved worldwide success because the broadband plasmon resonance matches the absorption band of the molecular analytes.…”
Section: Optical Application Of Localized Surface Plasmon: Random Nanmentioning
confidence: 99%
“…Its development and the initial efforts are compiled in two basic reference books. 1,2 An early report by Hartstein et al 3 showed that silver films could also be used to do surface-enhanced infrared (SEIR). However, SEIR did not reach the same level of development of SERS.…”
Section: Introductionmentioning
confidence: 99%
“…Since SEIR can only benefit from the |A(ω)| 2 factor, the total SEIR enhancement is expected to be orders of magnitude smaller than the enhancement factor observed in SERS. For instance, in the original report of Hartstein et al, 3 the maximum enhancement factor (EF) measured for SEIR was 20 using ATR and silver islands. Osawa and Ikeda 8 also report an electromagnetic EF of 20-30 for transmission IR spectra on silver islands and an enhancement factor of 20-50 for the case of reflectionabsorption SEIR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the last decade, it has been explored that SEIRA can be improved when resonant, tailored nanoantennas are used [48], instead of rough metallic surfaces where the effect has initially been discovered [49]. The polarization selective resonances of the investigated HDSC nanoantennas are particularly suitable for resonant SEIRA spectroscopy at mid-IR wavelengths.…”
Section: Resonant Seira and Spr Sensing Demonstrationmentioning
confidence: 99%